Sideways stories from Wayside School - Sachar, Louis. 1954-; Hockerman, Dennis (Chicago : Follett Pub. Co., 1978)
Humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
Keywords: Schools -- Fiction; Humorous stories